The Influence of Price Perception, Service Quality, Taste on Customer Satisfaction at Mie Gacoan in Bandar Lampung - Sari, Susi Amelia Dela; Bakti, Dadang Karya; Hasanah, Jamingatun (Journal of Business Management and Economic Development, 2025)
This study aims to determine whether price perception, service quality, and taste affect consumer satisfaction of Mie Gacoan in Bandar Lampung (survey on Gen Z consumers in Bandar Lampung). The type of research used in this study is explanatory research. This study uses a quantitative approach with the obtained using a purposive sampling technique and data collection is carried out by distributing questionnaires to 100 respondents, namely Gen Z consumers in Bandar Lampung. The data were analyzed using descriptive statistics and structural equation model analysis using SmartPLS 4.0 software. The data analysis techniques used are outer model tests, inner models, and hypothesis tests. The results of this study indicate that price perception and taste have a positive effect on consumer satisfaction. However, this service quality variable does not affect consumer satisfaction, this is because consumers have higher expectations of service quality than those given and consumers focus more on price and taste. Furthermore, simultaneously the variables of price perception, service quality, and taste have a positive effect on consumer satisfaction. Suggestions for further research are to add product quality variables, place atmosphere and facilities, and other variables that can affect consumer satisfaction. Then practitioners to be able to improve the quality of service that can affect the level of consumer satisfaction. by understanding the elements of service quality that are valued by consumers, such as employee environment, fast and responsive in serving consumers and employee appearance.